Characteristics of Korean personal names. Issue 1 (6th December 2012) - Kim, Sungwon; Cho, Seongyun
<x xml:space="preserve">Abstract</x> Korea, along with Asia at large, is producing more and more valuable academic materials. Furthermore, the demand for academic materials produced in non‐Western societies is increasing among English‐speaking users. In order to search among such material, users rely on keywords such as author names. However, Asian nations such as Korea and China have markedly different methods of writing personal names from Western naming traditions. Among these differences are name components, structure, writing customs, and distribution of surnames. These differences influence the Anglicization of Asian academic researchers' names, often leading to them being written in various fashions, unlike Western personal names. These inconsistent formats can often lead to difficulties in searching and finding academic materials for Western users unfamiliar with Korean and Asian personal names. This article presents methods for precisely understanding and categorizing Korean personal names in order to make academic materials by Korean authors easier to find for Westerners. As such, this article discusses characteristics particular to Korean personal names and furthermore analyzes how the personal names of Korean academic researchers are currently being written in English.